Application of Kruskal's Algorithm in Determining the Shortest Route Distance for Culinary Tourism in Mataram City - Gilang Primajati; M. Gunawan Supiarmo; Dita Oktavihari (Tinta Emas Publisher, 2025)
Mataram City as one of the tourist destination cities in West Nusa Tenggara has a variety of culinary attractions spread in various locations. The effectiveness of travel routes is an important factor in maximizing the culinary tourism experience, both in terms of travel time and cost efficiency. This research aims to apply Kruskal's Algorithm in determining the most effective culinary tourism travel route in Mataram City. Kruskal's algorithm, known as one of the methods in graph theory to find the minimum spanning tree (MST), is used to minimize the total travel distance between culinary location points. Location and distance data between culinary places were collected through field surveys and digital mapping. The results of the algorithm implementation show that the resulting route is able to connect all culinary points with a total travel distance that is more efficient than a random or conventional route of 15.09445 Km. Thus, the use of Kruskal Algorithm is proven effective as a solution in planning optimal culinary tourism routes in Mataram.